(untitled) (Bangladesh Journal of Agricultural Research, 2013)
The experiment was conducted at the research field of Agronomy Division, BARI, Joydebpur, Gazipur and ARS, Burirhat, Rangpur during consecutive two years of 2009-10 and 2010-11 to find out optimum fertilizer dose for hybrid maize-mukhikachu relay cropping system. Five fertilizer combinations viz, Recommended fertilizer of hybrid maize (RFM) + 112 kg N/ha, RFM + 25% recommended fertilizer of mukhikachu (RFK), RFM + 50% RFK, RFM + 75% RFK and RFM + 100% RFK were tested on hybrid maize-mukhikachu relay cropping system. Sole crops of hybrid maize (cv. BARI Hybrid Maize-5) and mukhikachu (cv. Bilashi) with their respective recommended fertilizer dose (maize: 255-55-140-40-6-2 kg/ha NPKSZnB and mukhikachu: 112-32-95-22 kg/ha NPKS) were included for comparison. Grain yield of sole maize with recommended fertilizer practice was identical with other fertilizer combinations at both the locations. Yield and yield components of mukhikachu under different fertilizer management practices increased with the increase of fertilizer levels up to RFM + 50% RFK and then decreased at both the locations. Edible yield of sole kachu with recommended fertilizer practice was the highest but it was identical to RFM + 50% RFK at both the locations. The highest maize equivalent yield (Joy: 24.26 t/ha, Buri: 31.56 t/ha) and gross return (Joy: Tk 291120/ha, Buri: Tk 378720/ha) was recorded in RFM + 50% RFK. But the highest gross margin (Joy: Tk 207035/ha, Buri: Tk 291570/ha) was obtained from RFM + 25% RFK at Joydebpur and from RFM + 50% RFK at Burirhat. The highest benefit cost ratio (Joy: 3.69, Buri: 4.64) was found from RFM + 112 kg N/ha at both the locations. The results revealed that recommended fertilizer dose (255-55-140-40-6-2kg/ha NPKSZnB) of hybrid maize plus 112 kg N/ha (extra) might be economically profitable for hybrid maize mukhikachu relay cropping system at both the locations. DOI: http://dx.doi.org/10.3329/bjar.v38i3.16975 Bangladesh J. Agril. Res. 38(3): 481-489, September 2013